Corneal stromal fibroblasts cell derived nanovesicles (CDN) in acute corneal haze context - Then, Ryan Yong Jian (Nanyang Technological University, 2024)
Corneal haze is the leading cause of blindness globally, severely impacting the quality of life of such individuals. Currently, corneal transplant remains as the most optimal treatment to restore vision in patients’ eyes with corneal haze. However, with a growing global demand for cornea donation, this has led to a severe shortage in the global supply of donor corneas. Hence there is a strong need for a new, effective, and deliverable alternative therapy to meet this medical need globally. In recent years, Cell Derived Nanovesicles, secreted from cells to mediate cell-cell communication, have become a new topic of growing interest for their therapeutic potential in corneal haze. In this study, the discussion will revolve around the therapeutic attributes of Cell Derived Nanovesicles to treat corneal haze. Cell Derived Nanovesicles are derived from cells, in particular Human Corneal Fibroblast stem cells, and possess antifibrotic, anti-inflammatory, and regenerative effects in injured corneas. The aim of the project is to develop an alternative treatment with Extracellular Vesicles in the form of eye drops (a hydrogel-based sustained delivery system) that is more appealing and less invasive compared to the current conventional, traditional methods. Bicinchoninic Acid Assay and Nanoparticle Tracking Analysis were conducted for protein characterization and particle size distribution analysis respectively. Size Exclusion Chromatography and Ultracentrifugation were performed for sample purification, while Slit-Lamp Biomicroscopy and Anterior Segment-Optical Coherence Tomography were used to provide visual imaging of the corneas during the in vivo test for monitoring the effectiveness of topical and subconjunctival treatments given. Cell Derived Nanovesicles were found to have a higher protein concentration and a comparable particle size and morphology compared to Natural Extracellular Vesicles. However, during the in vivo testing, both the Cell Derived Nanovesicles and Natural Extracellular Vesicles were unsuccessful in displaying any therapeutic healing properties to treating the corneal haze in the rat corneas, with corneal opacity progressively worsening each day post-surgery and treatment. Further research is required to comprehend the reason for the ineffectiveness of the Cell Derived Nanovesicle and Natural Extracellular Vesicle solution treatments by performing MTT assay on the Corneal Fibroblast cells.